Vsevolod E. Meyerhold’s (1874-1940) Presence in the World of Russian Cinema - Witczak, Jan Krzysztof (Sensus Historiae, 2025)
This essay is devoted to the importance of Vsevolod Meyerhold (1874–1940) for the development of theatre and cinematography in the pre-October and post-October Russian state. The profile described by the author has for years been the subject of increased interest of historians and cultural experts dealing with the complex, dramatic and extremely interesting history of artistic culture in the Land of Soviets. The article shows the process of Meyerhold’s dynamic cooperation with the pre-Stalinist Bolshevik regime and the tragic ending of his fate during the so-called Stalin’s Great Terror.